A comprehensive review on potential applications of metallic nanoparticles as antifungal therapies to combat human fungal diseases - Osama A. Madkhali (Elsevier, 2023)
Human pathogenic fungi are responsible for causing a range of infection types including mucosal, skin, and invasive infections. Life-threatening and invasive fungal infections (FIs) are responsible for mortality and morbidity, especially for individuals with compromised immune function. The number of currently available therapeutic agents against invasive FIs is limited compared to that against bacterial infections. In addition, the increased mortality and morbidity caused by FIs are linked to the limited number of available antifungal agents, antifungal resistance, and the increased toxicity of these agents. Currently available antifungal agents have several drawbacks in efficiency, efficacy, toxicity, activity spectrum, and selectivity. It has already been demonstrated with numerous metallic nanoparticles (MNPs) that these nanoparticles can serve as an effective and alternative solution as fungicidal agents. MNPs have great potential owing to their intrinsic antifungal properties and potential to deliver antifungal drugs. For instance, gold nanoparticles (AuNPs) have the capacity to disturb mitochondrial calcium homeostasis induced AuNP-mediated cell death in Candida albicans. In addition, both copper nanoparticles and copper oxide nanoparticles exerted significant suppressive properties against pathogenic fungi. Silver nanoparticles showed strong antifungal properties against numerous pathogenic fungi, such as Stachybotrys chartarum, Mortierella alpina, Chaetomium globosum, A. fumigatus, Cladosporium cladosporioides, Penicillium brevicompactum, Trichophyton rubrum, C. tropicalis, and C. albicans. Iron oxide nanoparticles showed potent antifungal activities against A. niger and P. chrysogenum. It has also been reported that zinc oxide nanoparticles can significantly inhibit fungal growth. These NPs have already exerted potent antifungal properties against a number of pathogenic fungal species including Candida, Aspergillus, Fusarium, and many others. Several strategies are currently used for the research and development of antifungal NPs including chemical modification of NPs and combination with the available drugs. This review has comprehensively presented the current and innovative antifungal approach using MNPs. Moreover, different types of MNPs, their physicochemical characteristics, and production techniques have been summarized in this review.